ANALISIS KIMIA BEBERAPA JENIS KAYU DARI SULAWESI UTARA - Gustan Pari; Setyani B Lestari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
This paper reported the result of chemical analysis of ten wood species from north Sulawesi.The result shows that holocelluloce content ranges from 55,64 to 65,42 percent, cellulose from 41,89 to 52,44 percent. Cellulose content of serianthes minahassae, pangium edule, lophopetalum javanicum, aglaia versteeghii and bischoffia javanica are higher than other species. Lignin content varies from 22,59 to 31,36 percent , pentosan from 16,92 to 19,61 percent. Lignin and pentosan content of all wood species examined are moderate and low. Ash content varies from 0,05 to 1,83 percent, silica from 0,04 to 0,4 percent. The solubility in cold water ranges 1,80 to 4,79 percent, in hot water from 2,91 to 5,16 percent, in sodium hydroxide from 11,06 to 19,21 percent and in alcohol benzene (1 : 2) from 6,08 to 9,08 percent, The axtractive contents, especially those soluble in alcohol benzene, of all wood species are in high extractives component class.Based on the cellulose and pentosan content all 10 wood species from north Sulawesi are suitable as raw material for pulp and paper industry.